Legal and institutional analysis of water resource management and development in Cambodia - Sithirith, Mak; Sok, Sao; De Silva, Sanjiv (WorldFish, 2023)
Cambodia has abundant water resources due to its geographies and the existence of 39 river basin systems. These rich natural resources are essential assets for the country. However, Cambodia has experienced toomuch water in the wet season and too little water in the dry season. Floods and droughts have undermined the development of Cambodia. Thus, improved water management is key to the development of Cambodia in the long run. The increased developments of infrastructures, irrigations, and hydropower powers in the Mekong region by riparian states including China, Thailand, Vietnam, and Laos have affected the Mekong River System and have altered the hydrological regimes of the Mekong River. These developments have further affected the flows and the volumes of water in Cambodia, particularly in Tonle Sap Lake. These developments have been driven by national interests, power relations, the geography of riparian states, and upstream and downstream politics. Furthermore, the rise of China has transformed the Mekong region into more regional cooperation frameworks such as MRC, GMS, and LMC. The US has concerned about the rise of China in the Mekong Region and scaled up its programs.